On the semilattice of all finitely generated subsemigroups of a semigroup - Арський, Нікіта (Київський національний університет імені Тараса Шевченка, 2024)
This article is dedicated to the upper semilattice FSub(S) of all finitely generated subsemigroups of a semigroup S. We prove some necessary and sufficient conditions for this semilattice to form a lattice or to be a complete semilattice and describe some of its atoms and dual atoms. Studied were also finitely generated semigroups, all of whose finitely generated subsemigroups are finite, and lattices of their finitely generated subsemigroups. A sufficient condition for such a semigroup to be finite was found. Pages of the article in the issue: 10 - 13 Language of the article: English

Ця стаття присвячена дослідженню верхньої напіврешітки FSub(S) всіх скінченно породжених піднапівгруп напівгрупи S. Знайдено деякі необхідні та достатні умови для того, щоб ця напіврешітка утворювала решітку або була повною, розглянуто її атоми та коатоми. Вивчаються також скінченно породжені напівгрупи, у яких всі власні скінченно породжені піднапівгрупи скінченні, та решітки їх скінченно породжених піднапівгруп. Знайдено достатню умову скінченності такої напівгрупи.
Про напіврешітку всіх скінченно породжених піднапівгруп напівгрупи
Keywords: semigroup; finitely generated semigroup; lattice of subsemigroups; semilattice of finitely generated subsemigroups; напівгрупа; скінченно породжена напівгрупа; решітка піднапівгруп; напіврешітка скінченно породжених піднапівгруп